Analysis of Pavement Maintenance Using Geographical Information System (GIS) - AHMAD SABRI, MUHAMMAD IMRAN SHAH; Sarif, Abdul Sukor (Progress in Engineering Application and Technology, 2023)
In the current world, the problems regarding pavement deterioration are still becoming a major concern since the road users are increasing day by day and they are demanding a good pathway and a good access road which can provide them comfort while driving and safety from disastrous accident. This study will be concerning about the pavement maintenance and rehabilitation system used in construction industry. The study will be focusing on the area which are frequently being maintained and repaired to identify the root of the occurring problems. As the world continues to follow the path of high technology in all sector including construction, the components of Industrial Revolution 4.0 will be the cofactor which catalyze the development of pavement maintenance. As example, the study will be utilizing a surveying software which is one of the technological advancement. QGIS software is one of the open-source software which can be utilized as a guidance in the form of map for rehabilitation work. Then, the data will be analyze using a method which is Pavement Condition Index (PCI) to evaluate the degree of degradation of asphalt concrete.